2023
DOI: 10.1007/s13157-023-01706-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Inundation Dynamics and Hydroperiods of Small, Isolated Wetlands Using a Machine Learning Approach

Abstract: The duration of inundation or saturation (i.e., hydroperiod) controls many wetland functions. In particular, it is a key determinant of whether a wetland will provide suitable breeding habitat for amphibians and other taxa that often have specific hydrologic requirements. Yet, scientists and land managers often are challenged by a lack of sufficient monitoring data to enable the understanding of the wetting and drying dynamics of small depressional wetlands. In this study, we present and evaluate an approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Using data until the end of March of each year, we predict whether a salt pan dries out ('desiccated') or remains 'inundated' during JASO of the same year. This binary classification scheme has already been used as the basis for modeling WE in a number of studies [87,90,91]. The simplicity of the inundation state in summer/fall, meaning its low temporal resolution, its low number of classes, and its low degree of mathematical abstraction (Section 3.1.2), in combination with our predictor setup and the RF algorithm, leads to relatively good model performance and model interpretability.…”
Section: Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Using data until the end of March of each year, we predict whether a salt pan dries out ('desiccated') or remains 'inundated' during JASO of the same year. This binary classification scheme has already been used as the basis for modeling WE in a number of studies [87,90,91]. The simplicity of the inundation state in summer/fall, meaning its low temporal resolution, its low number of classes, and its low degree of mathematical abstraction (Section 3.1.2), in combination with our predictor setup and the RF algorithm, leads to relatively good model performance and model interpretability.…”
Section: Model Setupmentioning
confidence: 99%
“…Advances in ML [70,71] have boosted the relevance of stochastic modeling for predicting lake WH [81][82][83][84][85]. Past research in modeling wetland inundation dynamics using ML methods is often restricted to using in situ measurements for identifying the presence of water [86,87]. Greater data availability provided by EO [39,88,89] has contributed to studies utilizing WE for modeling wetlands, although, to our knowledge, not for salt pans and in different temporal resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Cheng et al [19] discovered the significant role of independent small wetlands in nutrient retention in the USA. Riley et al [20] investigated the impact of hydrological cycle changes in small isolated wetlands on ecological functions. Atkinson et al [5] found that seasonal small wetlands at the landscape scale play a crucial role in maintaining biodiversity, with their hydrological characteristics influencing amphibian productivity and community dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The prerequisite for the successful protection and management of small wetlands is the construction of an accurate inventory of small wetlands using accurate maps (Aldous et al, 2021;Riley and Stillwell, 2023). Existing studies generally categorize and extract small wetlands using different classification methods based on low resolution remote sensing image data (Guan et al, 2022;Hibjur Rahaman et al, 2023;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%